À procura de olhares cúmplices: a produção social da paisagem na vila de Vizela - Silvano, Filomena (1994)
Cultura e arquitectura, Santiago, org. Paulo Castro, Seixas, Xerardo Pereira Pérez, Paula Mota Santos, pág. 135-147.